2020
DOI: 10.5935/1518-0557.20190058
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aging on semen parameters and sperm DNA fragmentation

Abstract: Introduction:This study aimed to look into possible correlations between male age and different sperm parameters derived from semen analysis and sperm deoxyribonucleic acid (DNA) fragmentation.Methods: This retrospective descriptive study included 2681 male patients who underwent semen analysis at Clínica Las Condes (CLC), Santiago, Chile, between January 2014 and May 2017; correlations between age and sperm parameters were analyzed.Results: Males above the age of 50 were significantly more likely to present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 23 publications
5
60
0
1
Order By: Relevance
“…An inverse relationship between male age and semen volume was identified in a large cohort study, with the decline becoming apparent at an average age of 35.5 years [120]. However, a more recent study found that the decline did not begin until after 50 years of age [98].…”
Section: Semen Volumementioning
confidence: 96%
See 3 more Smart Citations
“…An inverse relationship between male age and semen volume was identified in a large cohort study, with the decline becoming apparent at an average age of 35.5 years [120]. However, a more recent study found that the decline did not begin until after 50 years of age [98].…”
Section: Semen Volumementioning
confidence: 96%
“…Progressive motility, total motility and all sperm kinematics have been found to have negative correlations with increasing age [120]. In addition, Pino et al, found that the rate of progressive motility had a two-fold decrease in men > 50 in comparison with 40-50 year-old men [98]. However, there is little evidence for an association between sperm morphology and APA [62,105], when studied continuously stratified between men < 40 years old and ≥ 40 years old [120], nor between three different age groups (31-40, 41-50 and >50) [98].…”
Section: Sperm Motility Morphology and Viabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…SDF increases with age, starting in reproductive years and doubling between the ages of 20 and 60 years [ 41 42 43 ]. This association has been attributed to higher exposure to OS, defective sperm chromatin packaging, and disordered apoptosis that occur with aging [ 44 ].…”
Section: Origin Of Sperm Dna Fragmentationmentioning
confidence: 99%